23.5k views
1 vote
If f(x) = 3x^2 + 2 and g(x) = x^2- 9, find (f-g)(x).

O A. 4x2 - 7
O B. 2x2 +11
O c. 2x2 - 7
O D. 4x2 +11

User Umar Abbas
by
5.6k points

1 Answer

3 votes

Answer:


\boxed{\sf B. \ 2x^(2) + 11}

Given:

f(x) = 3x² + 2

g(x) = x² - 9

To Find:

(f - g)(x)

Explanation:


\sf (f -g)(x) = f(x) - g(x) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =(3x^(2) + 2) - (x^(2) - 9) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =3x^(2) + 2 - x^(2) + 9 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =3x^(2) - x^(2) + 2 + 9 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =(3x^(2) - x^(2)) + (2 + 9) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =2x^(2) + (2 + 9) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =2x^(2) + 11

User TheBigBadBoy
by
5.9k points